Produção sustentável de leite bovino em área de proteção ambiental: aplicação da análise energética no município de Torre de Pedra/SP - Silva, Marísia Cristina da [UNESP] (2014)
Agricultural activity is considered one of main sources of food supply for humanity. It contributes to local, regional, and national development. However, the activity results in significant adverse environmental impacts when it is not developed based on social, economical and environmental sustainability aspects. The need of an efficient use of natural resources with a minimal environmental impact poses as a challenge when it is related to the solution of problems resulted from the use of energy sources coming from the environment. The establishment of organized productive systems for local farmers provides better management of local natural resources besides favoring, from a sustainability perspective, a better economic organization of the environment. The town of Torre de Pedra / SP is part of the Environmental Protection Area Corumbataí-Botucatu-Tejupa, Perimeter Botucatu The region has a traditional vocation for dairy farm production and it presents problems ranging from environmental to socioeconomic aspects. This project focus on the identification and analysis, with regards to energy, of bovine milk production systems in family farms located in Torre de Pedra/SP. There were performed technical visits to the farms in order to gather quantitative and qualitative data. The farmers were asked to respond to semi-structured questionnaires in order to help us to establish detailed conditions for the analysis of production systems to be studied. Thus, potential drawbacks related to the external dependence on non-renewable energy sources were identified based on the years 2011 and 2012. The direct energy, coming from biological and fossil fuel sources, and indirect energy coming from industrial sources, were measured based on the data collection as well as the energetic outflows of two 4 ...